2018
DOI: 10.17165/tp.2018.2.9
|View full text |Cite
|
Sign up to set email alerts
|

Mint(h)atréning, a felsőoktatás fenegyereke – koncepció és teszt bemutatása

Abstract: Mint(h)atréning, a felsőoktatás fenegyereke-koncepció és teszt bemutatása Az oktatás a tréninget a gyakorlatorientált képzési formák egyikeként kezdte alkalmazni. Felvetődik viszont, hogy miképpen hasznosul leginkább a tréning a gazdasági oktatásban. Egyik oldalról készségeket és kompetenciát fejleszt, de szakmai előképzettségek nélkül, kérdéses, hogy a kapott tudás valóban interpretációs szinten beépülne a hallgatók eszköztárába. Másik oldalról a céges szakemberek, vezetők, főként a HR területén elhelyezkedők… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 1 publication
1
20
0
Order By: Relevance
“…These are discussed in Section 3. We also compare theoretically calculated log(gf ) values of Kurucz (2007) and recent results of Wang et al (2014), which combine measured lifetimes and theoretical branching fractions, with our new data, and confirm that experimentally measured log(gf) values are more reliable where these exist. Additionally, we provide log (gf ) values for 13 lines that have not been reported in any previous study, nine of which are in the infrared at wavelengths longer than 1.6 μm, which was the longest wavelength for any previously reported log(gf ) value in V I (Whaling et al 1985).…”
Section: Introductionsupporting
confidence: 81%
See 3 more Smart Citations
“…These are discussed in Section 3. We also compare theoretically calculated log(gf ) values of Kurucz (2007) and recent results of Wang et al (2014), which combine measured lifetimes and theoretical branching fractions, with our new data, and confirm that experimentally measured log(gf) values are more reliable where these exist. Additionally, we provide log (gf ) values for 13 lines that have not been reported in any previous study, nine of which are in the infrared at wavelengths longer than 1.6 μm, which was the longest wavelength for any previously reported log(gf ) value in V I (Whaling et al 1985).…”
Section: Introductionsupporting
confidence: 81%
“…Their predicted contribution to the total BF was assigned to a "residual" value, which was used to scale the sum over l of I ul . The predicted BFs of Kurucz (2007) are used because we found these to be more reliable than those of Wang et al (2014) due to the strong cancellation effect reported by Wang et al (2014) affecting some of the transitions, in particular those depopulating the lowest excited odd-parity levels. Figure 4 shows comparisons of our measured BFs with those of Kurucz (2007) and Wang et al (2014).…”
Section: Log(gf) Measurementsmentioning
confidence: 91%
See 2 more Smart Citations
“…(LTE) model. In the new version, the new iron atomic data computed by Kurucz (2009) was incorporated. We derived the stellar parameters of the four r-II stars via the spectroscopic approach, namely, the effective temperature T eff was determined by requiring the equilibrium between the excitation and iron abundance from Fe I lines, and the surface gravity log g was derived from the ionization equilibrium of Fe I and Fe II.…”
Section: Model Atmospheres and Stellar Parametersmentioning
confidence: 99%